The Freebooters of the Wilderness - Laut, Agnes C., 1871-1936 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Freebooters of the Wilderness" by Agnes C. Laut is a historical narrative written in the early 20th century. The book addresses themes of lawlessness and corruption in the American West, intertwining fiction with real events and figures from the period. It revolves around characters such as Wayland, a Forest Ranger, and Eleanor, the daughter of a sheep rancher, as they confront the challenges posed by various forces that threaten public land and justice. At the start of the story, we are introduced to Wayland, who grapples with the question of whether to stand up and fight against the injustices around him or to abandon the struggle for self-preservation. This inner conflict is heightened by his complicating feelings for Eleanor, who embodies both Eastern culture and Western directness. Their dialogue brings to light the harsh realities of corruption among powerful figures like Senator Moyese, who represents interests that undermine the rights of common people. As their relationship develops amid the backdrop of political intrigue and personal stakes, the opening chapters set the stage for a larger discussion about morality, sacrifice, and the challenges of doing what is right in the face of overwhelming odds. (This is an automatically generated summary.)
Release date is 2006-04-04
E-text prepared by Al Haines
Keywords: Frontier and pioneer life -- West (U.S.) -- Fiction